Examining the Influence of Brand Image and Brand Trust on Customer Satisfaction and Loyalty: A Study on Wardah Cosmetics - Luthfitawati, Rosaliana; Sutejo, Bambang (Manunggal Halim Jaya, 2026)
This study is about the impact of brand image and trust on customer satisfaction, and the influence of customer satisfaction on customer loyalty, which is important to maintain the competitiveness of beauty products such as Wardah, especially among garment workers. Data were gathered via questionnaires with 62 respondents, selected using the Roscoe Theory and purposive sampling. The questionnaires in the form are the primary data source in the study. This research uses a quantitative approach, testing SPSS 25 for all answers to the research sample. The findings indicate that brand image and brand trust have a positive and significant effect on customer satisfaction. Customer satisfaction has a positive and significant effect on customer loyalty. Overall, this study strengthens the understanding of how brand image and trust influence customer satisfaction, increasing customer loyalty towards Wardah products. This finding has contributed to understanding an effective marketing strategy for building satisfaction and customer loyalty in the cosmetic industry.